2000
DOI: 10.1111/j.1525-1373.2000.22507.x
|View full text |Cite
|
Sign up to set email alerts
|

Promotive Effects of a Silk Film on Epidermal Recovery from Full‐Thickness Skin Wounds

Abstract: Abstract. We examined the effects of the transparent fibroin film (silk film) on full‐thickness skin wounds. Full‐thickness dermatotomies (15 mm × 9 mm) were prepared on the dorsal wall of CRJ:CD‐1 nu/nu (ICR nu/nu) mice. The area of the wounds dressed with silk film was reduced to 10% of that made by the dermatotomy 14 days after the dermatotomy and were covered with regenerated epidermis 21 days after the dermatotomy. In contrast, less recovery and epidermal regeneration were found 14 days after dermatotomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 20 publications
0
47
0
Order By: Relevance
“…Studies have confirmed that silk fibroin films support the adhesion and proliferation of a variety of cells in vitro, and behaves in a similar way to that under in vitro conditions. 13,14,[24][25][26] Striations at micron and submicron level can be printed on the surface of the silk films, which guide the cells and the subsequent arrangement of the extracellular matrix. 13,25,27,28 In addition, the silk fibroin can also be made into optical transparent films.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed that silk fibroin films support the adhesion and proliferation of a variety of cells in vitro, and behaves in a similar way to that under in vitro conditions. 13,14,[24][25][26] Striations at micron and submicron level can be printed on the surface of the silk films, which guide the cells and the subsequent arrangement of the extracellular matrix. 13,25,27,28 In addition, the silk fibroin can also be made into optical transparent films.…”
Section: Discussionmentioning
confidence: 99%
“…7) It is assumed that the highly hydrophilic nature of sericin contributes to the observed wound healing effect by maintaining a moist environment and absorbing excess exudate from wounds. The usefulness of sericin as a film wound dressing was also suggested by Tsubouchi et al: the incorporation of sericin in fibroin films, whose availability as a wound dressing has been examined, 8,9) improved the flexibility of the films. 10) For wound dressings, flexibility is an important factor to enable close and soft contact with the skin.…”
mentioning
confidence: 95%
“…Previous studies showed that two-dimensional silk fibroin films have good biocompatibility [6,[20][21][22]. Recent progress in processing techniques has yielded three-dimensional porous silk fibroin scaffolds with control of morphological and structural features [23][24][25].…”
Section: Introductionmentioning
confidence: 99%